Selective emitters prepared by high density plasma immersion ion implantation (HD-PIII) in silicon wafer based solar cell - Seow, Leslie Kai Tong. (2013)
Plasma Ion Immersion Implantation is a rapidly developing modification technique used for doping the near-surface regions of materials by implanting energetic ions from plasma, which will surround the sample in the vacuum chamber. This technique is widely known for its accuracy for dopant concentration and junction depth at implanted regions, and its cost saving properties.